Houses of Experiment: Making Space for Science in Republican China. Issue 3 (1st September 2016) - Fu, Jia-Chen
Abstract : This essay explores the scientific lives of two Republican-period institutions: the Henry Lester Institute of Medical Research, based in Shanghai; and the Chongqing No. 3 Children's Home. Despite their differences, these two spaces sheltered and nurtured scientific experimentation and functioned as heterotopic sites that controlled who could produce scientific knowledge and which kinds of scientific objects could become visible. By examining closely the research work of Bernard E. Read, Stephen M. K. Hu, and the team of nutrition scientists from National Jiangsu Medical College, this article argues that how space became hospitable for scientific experiment and how science refashioned space were mutually constitutive processes. This process of coproduction was critical to and, at times, contested through expressions of expertise.